2022
DOI: 10.18502/ijph.v51i5.9428
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of the Green Microalgae Isolated from the Persian Gulf

Abstract: Background: We aimed to investigate the antibacterial activity of Persian Gulf microalgae extracts on some Gram-positive and negative bacterial species in order to find new compounds with antibacterial activity. Methods: After sampling microalgae from December 2020 to April 2021 from the northernmost part of Qeshm Island in Persian Gulf, the antibacterial activity of methanolic and ethyl acetate extract of microalgae were tested in three concentrations of 125, 250, and 500 mg/ml on Gram-positive bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The extracts at concentrations of 10-15 mg/ml showed bacterial inhibition (7-18 mm) with minimal biomass utilisation. These results are notably akin to those derived from other microalgae species [16,17,18] and are in the vicinity of outcomes for methanol extracts from more substantial macroalgae biomass [19,20]. P. kessleri exhibited the most significant antibacterial effect against B. subtilis and S. aureus, with a lesser effect noted against K. pneumoniae.…”
Section: Resultsmentioning
confidence: 61%
“…The extracts at concentrations of 10-15 mg/ml showed bacterial inhibition (7-18 mm) with minimal biomass utilisation. These results are notably akin to those derived from other microalgae species [16,17,18] and are in the vicinity of outcomes for methanol extracts from more substantial macroalgae biomass [19,20]. P. kessleri exhibited the most significant antibacterial effect against B. subtilis and S. aureus, with a lesser effect noted against K. pneumoniae.…”
Section: Resultsmentioning
confidence: 61%
“…The biocidal effects of C. onubensis extracts were higher than those of extracts of other microalgae species. Saeed Niazi et al [ 39 ] investigated the antimicrobial potential of the methanol extracts of the green microalgae isolated from the Persian Gulf and highlighted their effects against Staphylococcus aureus , Bacillus Cereus , Escherichia coli , and Pseudomonas aeruginosa (the MIC was 0.75, 1.5, 3, and 6 mg/mL and MBC was 1.5, 1.5, and 6 mg/mL, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…A study on the manifestation of antibacterial activity of an L. sp. extract against MSSA and MRSA exclusively followed the extract’s preceding laser treatment [ 17 , 18 , 19 ]. It has been demonstrated that the cyanobacterium P. agardhii exhibits estrogenic activity [ 20 ].…”
Section: Discussionmentioning
confidence: 99%